(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
Due to the pandemic caused by the new coronavirus (SARS-CoV-2) and its rapid geographical dispersion responsible for the spread of COVID-19 disease, the adoption of risk prevention and containment strategies were established. Social distancing was one of these measures, which resulted in major impacts on the educational system, causing the suspension of face-to-face classes for an indefinite period. Considering this scenario, institutions and teachers sought strategies for remote educational activities as an alternative to keep students active and close. This study contextualizes Emergency Remote Education and analyzes didactic practices, as well as the results of a free online course on creative fashion illustration. The type of research used was descriptive, and as a method of data collection, the case study. The results expose the experience with remote teaching, procedures, resources and the contents that made up the course.